Simple and effective label-free electrochemical immunoassay for carbohydrate antigen 19-9 based on polythionine-Au composites as enhanced sensing signals for detecting different clinical samples - Huang ZJ (Dove Medical Press, 2017)
Zhengjun Huang,1,2 Zhouqian Jiang,1,2 Chengfei Zhao,1,2 Wendi Han,3 Liqing Lin,1,2 Ailin Liu,1,2 Shaohuang Weng,1,2 Xinhua Lin1,2 1Department of Pharmaceutical Analysis, School of Pharmacy, Fujian Medical University, 2Higher Educational Key Laboratory for Nano Biomedical Technology of Fujian Province, 3Department of Pharmacy, The First Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China Abstract: Carbohydrate antigen 19-9 (CA19-9) is an important biomarker for the early diagnosis and clinical monitoring of pancreatic cancer. Reliable, simple, and accurate methods for the detection of CA19-9 are still urgently needed. In this study, polythionine-Au composites (AuNPs@PThi) were designed and prepared through one-pot reaction using HAuCl4 as the co-oxidant and raw material in thionine solution containing FeCl3 as the oxidant. AuNPs@PThi-immobilized glassy carbon electrode was used as a sensitive redox probe for electrochemical interface. AuNPs@PThi not only favored the amplification of electrochemical signals but also facilitated excellent environmental friendliness for bioassay. Maximizing the electrochemical properties of AuNPs@PThi, an effective label-free electrochemical immunoassay for the ultrasensitive and reliable detection of CA19-9 was developed. Under optimal conditions, the linear range of the proposed immunosensor was estimated to range from 6.5 to 520 U/mL, with a detection limit of 0.26 U/mL at a signal-to-noise ratio of 3. The prepared immunosensor for CA19-9 detection showed high sensitivity, stability, and reproducibility. Furthermore, the fabricated immunosensor based on AuNPs@PThi can effectively detect and distinguish clinical serum samples of pancreatic cancer and normal control with accuracy and convenience. Keywords: polythionine-Au composites, label-free electrochemical immunoassay, carbohydrate antigen 19-9, clinical sample, signal amplification